Collaboration in Environmental Conflict Management and Decision-Making: Comparing Best Practices With Insights From Collaborative Learning Work - Walker, Gregg B.; Daniels, Steven E. (Frontiers in Communication, 2019)
For much of the past three decades, when environmental or natural resource conflicts have emerged, diverse parties (government agencies, stakeholder organizations, and citizens) have often sought an alternative to adversarial battles. They have turned to collaboration, and in so doing, have attempted to work through conflicts to find common ground and make sound decisions. And in so doing their experiences have given rise to the development of “best practices” for conducting collaborative work. This essay considers three sets of best practices for collaboration and compares through practices with the authors’ twenty-seven years of Collaborative Learning fieldwork. When insights from Collaborative Learning projects are combined with a collective set of best practices, eighteen areas emerge to guide collaborative efforts.